Comparative pathogenicity of infectious bronchitis virus Massachusetts and Delmarva (DMV/1639) genotypes in laying hens - Farooq, Muhammad; Abd-Elsalam, Reham M.; Ratcliff, Natalya; Hassan, Mohamed S. H.; Najimudeen, Shahnas M.; Cork, Susan C.; Checkley, Sylvia; Niu, Yan Dong; Abdul-Careem, Mohamed Faizal (Frontiers in Veterinary Science, 2024)
Infectious bronchitis (IB) is a highly contagious and acute viral disease of chickens caused by the infectious bronchitis virus (IBV) of the family Coronaviridae. Even with extensive vaccination against IB by the poultry industry, occurrence of new IBV genotypes is a continuous challenge encountered by the global poultry industry. This experiment was designed to compare the pathogenicity of two IBV strains belonging to Massachusetts (Mass) and Delmarva DMV/1639 genotypes. Specific pathogen-free laying hens were challenged during the peak of production ( 30weeks) keeping a mock-infected control group. During 21 days of observation following infection, a significant drop in egg production with miss-shaped and soft shells was observed in the DMV/1639 IBV-infected hens only. The DMV/1639 IBV infected group showed prolonged and higher cloacal viral shedding compared to the Mass IBV infected group. At the end of the study (21 days post-infection), the viral genome loads in the respiratory, urogenital, and immune tissues were significantly higher in the DMV/1639 IBV infected group compared to the Mass IBV infected group. Macroscopic lesions such as distorted ova leading to egg peritonitis were observed only in the DMV/1639 infected group. Moreover, microscopic lesion scores were significantly higher in the lung, kidney, cecal tonsils, and oviduct of the DMV/1639 IBV infected group compared to the Mass IBV infected group. Finally, the apoptosis index in the kidney, ovary, magnum, isthmus, and shell gland was significantly higher in the DMV/1639 IBV-infected group compared to the control and Mass infected groups. This study examined the pathogenicity of two IBV genotypes that are impacting the layer industry in North America.